English Exposure in English-Speaking Environment to Vocabulary Acquisition in Junior High School.: Paparan Bahasa Inggris di Lingkungan Berbahasa Inggris Terhadap Akuisisi Kosa Kata Baru di SMP . - Yusfiah Yasmin; Mujad Didien Afandi; Novi Rahmania Aquariza; Nailul Authar (Universitas Nahdlatul Ulama Surabaya, 2024)
English is a language that is needed in this day and age. Therefore, exposure is very necessary for students so that they are familiar with it for their future preparations. This research was conducted to determine the exposure of English students at Mts Bilingual Pucang to the acquisition of new vocabulary. Qualitative descriptive is the research method used in this research. The aim of this research is to describe exposure to English in an English-speaking environment on vocabulary acquisition. This research uses several instruments to collect data such as observation sheets to observe activities at school, questionnaires and interviews to determine students' perceptions of being in an English-speaking environment. The results of this research are based on observation data where students can acquire new vocabulary because they receive continuous exposure to English and are supported by an immersive environment. In addition, students are motivated to use English at school because of the positive impact they get, so that students enjoy the English-speaking environment.